(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper reveals how the life practice of Bun- do kanduang in the Minangkabau community after the decline in the existence of the Rumah Gadang and how the role and function of Bundo kanduang after leaving the Rumah Gadang. This type of research is field research conducted at Kenagarian Balai Gurah, with data col- lection techniques through in-depth interviews with Bundo Kanduang, traditional leaders, religious leaders, and Wali Nagari Balai Gurah.